Design of a safety operational envelope protection system for a submarine. (15th January 2018) - Park, Jong-Yong; Kim, Nakwan
Abstract: A safety operational envelope (SOE) is an area that guarantees the safety of a submarine from accidents, such as jamming and flooding. In this study, a submarine envelope protection system (EPS) was designed to prevent submarine excursion from the SOE. Modeling of the hull force, propeller force, and main ballast tank blowing was performed. The SOE was established based on a crash stop and emergency rising maneuver simulation. In the estimation model, a linear compensator and neural network are employed to estimate the submarine dynamics. The command limit is calculated using the estimation model and the dynamic trim algorithm, and it is restricted by the limit avoidance. The EPS was applied to a submarine maneuvering simulation program and its performance was verified by a depth change simulation. The designed EPS prevents the submarine from exceeding the limit boundary and the control system can thereby enhance the operational stability. Highlights: The aim of this study is to design an envelope protection system that ensures the submarine maintenance within a predefined safety operational envelope (SOE). The SOE of the submarine is determined by the emergency rising maneuver and crash-stop simulation results. The linear approximation model, linear compensator, and neural network are adopted for closed-loop dynamics estimation of limit parameters, such as speed, depth, and pitch angle. The dynamic trim algorithm and fixed-point iteration method are adopted for limit detection. The limit avoidance scheme is based on a command-limiting architecture that is designed to protect excursions in the limit parameters.